Identificación de polinizadores y su eficiencia en el cuajado de frutos de la chirimoya en poblaciones silvestres de la provincia de Loja. - Quezada Pucha, Alex Xavier (2018)
In Loja province Annona cherimola Mill is one of the endemic species more representative, finding a great number of ecotypes in the different wild formed forests. This species in spite of having an exquisite flavor and nourishing content, and being a fruit with a high potential for the export, has been little taken advantage from the economic and reproductive point of view, since the existing information brings over of the diversity of the natural native pollinating and as these influence fruit set of cherimoya is out of date, having like proved fruits of low quality and in some cases a deficient pollination of its flowers. With the study of the diversity of floral visitors, it was possible to verify that the pollinating insects present in the sectors of study were the genus: Colopterus, Carpophilus, Epuraea, Orius and Trip and genus and species: Mimemodes monstrosus and Stator testudinarius. The investigation also determined that the sectors Sta. Teresa and Chirimoyal of the Calvas' canton showed a diversity and specific dominance it a low, unlike the sector Nangora, canton of Loja that it presented a diversity and medium specific dominance, whereas 3 sectors presented an uniform distribution of species. In addition, it was shown that the efficiency of the floral visitors in the natural pollination had a percentage of persistence in fruit set of fruits medium, showing that the intervention of these pollinators have positive influence on the fructification of cherimoya.